THE TEMPERATURE OF SMOLDERING TOBACCO. THE METHOD OF ITS MEASUREMENT BY THERMOCOUPLES FOR THE SOLUTION OF THE QUESTION OF THE CAUSE OF THE FIRE - A. Saklantiy; I. Taubkin (Теория и практика судебной экспертизы, 2016)
The method of measuring the temperature of smoldering tobacco by thermocouples and its values are given for some cigarette brands defined by this method.